(The) Death (of) the Animator, or: The Felicity of Felix, Part II - Alan Cholodenko (Animation Journal, 2007)
A Difficulty in the Path of Animation Studies2 Before I set out on the work of this paper (Part II) I will briefly reprise Part I to orient the reader. Subtitled ‘Kingdom of Shadows’, Part I argues the singular importance of animation to cinema and to film, and the singular importance of death to animation, hence to cinema and to film. Part I is a return engagement with Tom Gunning’s canonical article, ‘An Aesthetic of Astonishment: Early Film and the (In)credulous Spectator’, an article establishing Gunning’s notion of the cinema of attractions as the now orthodox understanding of what early cinema is in Film Studies. I had first taken up his article in my piece ‘The Crypt, the Haunted House, of Cinema’, published in Cultural Studies Review (2004). That article extends, qualifies and recasts Gunning’s formulation of his cinema of attractions, including by rereading Maxim Gorky’s review of his experience of the Lumière Bros cinematograph at the Nizhni-Novgorod fair in Russia July 4, 1896, a review that is for Gunning as for ourself not only the first substantial account of cinema but one that is paradigmatic in and for its understanding of it. The most significant point in this return engagement with Gunning is that in elaborating the nature of his cinema of attractions, Gunning unwittingly makes animation the first attraction of cinema, the last attraction of cinema and the enduring attraction of cinema, thereby likewise unwittingly makes his cinema of attractions animation of attractions. <!--more--> In so doing, Gunning confirms our still apparently radical notion, articulated in so many publications, that not only is animation a form of film, all film, including cinema by definition, is a form of animation. For the largest reach on what this animation of attractions – of shocks, thrills and chills – and these attractions of animation would be, it is to Gorky’s review we turned, with its famous opening lines: Last night I was in the Kingdom of Shadows. If you only knew how strange it is to be there. It is a world without sound, without colour. Everything there – the earth, the trees, the people, the water and the air – is dipped in monotonous grey. Grey rays of the sun across the grey sky, grey eyes in grey faces, and the leaves of the trees are ashen grey. It is not life but its shadow, it is not motion but its soundless spectre. Here I shall try to explain myself, lest I be suspected of madness or indulgence in symbolism. I was at Aumont’s and saw Lumière’s cinématograph – moving photography. (Gorky, 1996 p.5) ‘Not life but its shadow’, ‘not motion but its soundless spectre’. As I argue in ‘The Crypt, the Haunted House, of Cinema’, Gorky’s paradigmatic experience of cinema makes the spectre ‘ur’ figure of cinema and the uncanny ‘ur’ experience of cinema. Put simply, the first, last and enduring attraction of cinema as form of animation as form of what we call the animatic is the uncanny reanimation of the dead as living dead, of what after Jacques Derrida we call lifedeath. Indeed, we propose in that article that what Gorky describes as his experience of cinema would be the effect of the spectre, the spectre of cinema and its whole set of affects/shocks/attractions composing the ‘ur’ experience of cinema as form of animation as form of the animatic for us – making that ‘ur’ experience what we call the Cryptic Complex of the uncanny, the return of death as spectre, endless mourning and melancholia and cryptic incorporation. Such would be the primal experience of cinema, a shocking, traumatic experience of animation, of reanimation – of the animation, reanimation, of death – that even the sophisticated Gorky rehearses for us in his for us account of the unaccountable, account of Freud’s most striking example of the uncanny – haunting – the ‘relation to death and dead bodies, to the return of the dead, and to spirits and ghosts’, as Derrida puts it (Derrida, 1994 p.195, note 38), making cinema – the crypt, the haunted house, of cinema – privileged example of Freud’s ‘unheimlich’ (haunted) house. House of the living dead, a house, never a home. (Part I of this article is published in “Animated Dialogues, Melbourne” edition of Animation Studies). I Taking off from our claim that it is the uncanny sense of the dead returning to life and at the same time the living returning to death, reanimated likewise as living dead, that informs Maxim Gorky’s response to his first sight and experience of cinema – a response that repeatedly characterises these living moving forms as shadows, spectres – the work of the first section of Part II is to extend the reach of this spectre for any thinking of animation. Then, in the second section, we will cast its shadow over something that has been fundamental to animation studies, the thinking of the subject as form of presence, of essence, as unified and as centred, a subject that for animation studies achieves its fullest expression in the figure of the animator. It is to etymology that we now turn to embark upon the work of this first section. While the word animation is rooted in Latin anima, it goes by another name in Greek, whose significance for our argument cannot be overstated. The ‘equivalent’ for anima in Greek is psuché. Psuché, as Jean-Pierre Vernant tells us (Vernant, 1991, p.186), is a form of eidolon. Eidolon in Greek means double. psuché is the simulacral figure, the spectre, that leaves the body of the dead one to wander as flitting shade in Hades, which is, not insignificantly for us, Gorky’s Kingdom of Shadows, his (for us) Kingdom of Cinema, of Animation. No matter that Plato ‘turned’ psuché the spectre into psyche the soul, he for us was never able to master the spectre – who could?! – a failure reanimated in every attempt by all his avatars to be master of the games played by the world and its objects, including master of cinema, of film animation – be it maker, analyst, theorist, spectator – an aspiration and failure so chillingly marked and victoriously mocked by that psuché of Norman Bates/mother/skull that ‘ends’ Hitchcock’s aptly titled Psycho (1960), that shade/shadow laughing at all efforts to psychoanalyse, explain and rationalise it and turning the subject and all it ‘commands’ towards what is superior, anterior and never not returning to it: death.3 Which is to say that psuché, the hauntological, spectres psyche, the ontological, as it does all rooted in psyche and the ontological, including psychoanalysis, psychological narrative (including the ‘integration’ defining Gunning’s cinema of narrative integration), the Imaginary thought as plenum, the subject, identity, self-identity and the individual thought as forms of presence, essence, wholeness, etc., making them the special case, the reduced, conditional form, of psuché, of the hauntological. Here, at the ‘origin’ of animation, psuché as spectral simulacral eidolon animates, spectring and exorcising with its apparition, its trompe l’oeil, its nothingness, all forms of ontology, including all efforts to ontologise ‘itself’, most notably, as we mentioned, Plato’s reversal and ontologizing of the Homeric psuché as soul, inherited in the Latin anima (air, breath, soul, spirit, mind) and in the soul of Christianity.4 And in animation thought as ontological, that is, of the order of presence, essence, the Platonic psyche, the Latin anima, the soul of Christianity. Animation – as what we call the animatic (the very singularity of animation, anterior and superior to animation, the condition of possibility and at the same time impossibility of animation, at once the inanimation in and of animation and animation in and of inanimation, that nonessence at once enabling and disenabling animation as essence, at once the life of death and death of life) – is of the order of the hauntological, of psuché, the Homeric eidolon – of at once this world and ‘an inaccessible elsewhere’ (Vernant, 1991 p.187). It marks for us what Gunning calls (though with what appears to be a decidedly disparaging idea of cinematic illusion) ‘the hollow centre of the cinematic illusion’ (Gunning, 1989, 42), for us the atopos of cryptic incorporation, the Cryptic Complex – the dead point, blind spot, black hole that marks for Baudrillard ‘that absence at the heart of the system’, ‘the Nothing which haunts it’, ‘that shadow running alongside it’ (Baudrillard, 2001 p.149).5 Which means that cinema as form of animation as form of the animatic calls not simply for a psychoanalysis but a ‘psuché-“analysis”’, an analysis by definition impossible of resolution, for psuché, even as it enables such a possibility, at the same time spells its death, as it does that of a science of the psyche, ie., psychology, which would be an impossible science of the double, of spectres, turning that ‘science’ into a séance. We therefore propose that what Gorky ‘saw’ and so terrified him, so much so that he sought to repress, exclude and disavow it, were psuchai, ‘saw’ his own psuché, ‘saw’ the image of psuché and the psuché that is the image, the image ‘as such’ – the image not merely as appearance (for Plato) but as apparition – and ‘saw’ the ‘blind spot’ ‘as such’ – the psuché ‘as such’ – of the image as apparition.6 In other words, he ‘saw’ death,6 the fate that awaits us all, a fate never not happening, as it is to Gilles Deleuze’s philosopher, in the here and now, thanks to animation, to the animatic.8 Put simply, death spectres cinema, film animation, indeed animation ‘as such’, as the animatic. Thanks to cinema, to film animation, reanimating animation in multiplicitous ways, including reanimating Robertson’s Fantasmagorie and its ‘climactic’ image – none other than ‘The Fate that Awaits Us All’ - death is always already returned, a fait (fate!) accompli, the rule of animation as the animatic over cinema from its advent – cinema as Kingdom of Shadows, as crypt, as haunted house, as Gorky’s ‘train of shadows’ (Gorky, 1996 p.5), marking cinema’s allegiance to the dark side, its nature as one of the unhallowed arts, as occult science, as ‘child of the night’, even as it privileges genres associated with and figures drawn from the crypt, never not allied with it, with cryptic incorporation, with haunting – the ‘children of the night’, the undead. So, to reiterate a key conclusion from Part I of my paper, ironically, paradoxically, animation as the animatic privileges death over life, and makes every encounter with cinema as form of animation as form of the animatic an encounter with death. Thanks to the animatic, the excluded, the ‘blind spot’ – animation – and the excluded of all excluded, the ‘blind spot’ of the ‘blind spot’ – death – are always already reanimated and reanimating, are always already back. II Here our second issue of singular importance for animation studies (one we have implicitly canvassed already). That issue is the way animation studies places the individual at the ‘very core’ of animation in the figure of the animator, envisioned as all-controlling, master subject, the subject par excellence. It does so and for a field that reads animation almost exclusively through the subject and the subject’s desires, intentions, affects and effects, where identity is the key if not sole model, focus and attractor, strangely drawing to it, while at the same time subordinating to it, all else, at the same time ignoring the other, and for us superior, side of the ‘equation’: the object and its games, the games of the world, with which for us animation has privileged, superior, indeed singular, relation, marked in our very figure of the animatic. Likewise, any thinking of cinema and animation cannot delimit itself to treating them as only modes of production and appearance9 but must as well consider them as modes of seduction, dissemination, disappearance and death – likewise for us superior processes associated with the animatic. For us, animation studies, in largely reading up to today all through the subject and/as individual, and through the animator as the very essence of the subject and/as individual, and through identity and self-identity, propounds and is wedded to an understanding partial at best and radically deficient at worst. And more, to an understanding that is dramatically, and seemingly unknowingly, retrograde in terms of Film Studies, film criticism and film theory and their history insofar as it – animation studies – poses, embraces and models the animator as the very limit case of the filmmaker, that is, as author. To use the French term, as auteur, that invention of French film criticism of the 1950s that spread to the English-speaking world and was the watchword of film writing in the ’50s and ’60s, that is, until the advent of late ’60s French film theory and its conjugations with structuralism and structural linguistics, Althusserian Marxism, Saussurean and Barthesian semiology, Lacanian psychoanalysis, etc., each of which ‘knowledges’ brought with them massive critiques of the notion of the auteur, critiques informing late ’60s French film theory and the English film theory derived from it, critiques which ‘poststructuralist’ and ‘postmodernist’ approaches perpetuated and which approaches for us offer the richest ways to theorise animation, approaches the most isomorphic with animation and the animatic, approaches the most informed by and performing them. Only a small number of animation scholars seem aware of such approaches, an even smaller number mobilise them in their work. For us, it is incumbent upon animation scholars to acquaint themselves with (such) film theory and its history rather than ignore it, for animation studies and Film Studies are for us inextricably commingled, despite the general lack of acknowledgement of that on the part of either. So for animation studies, the animator would be the very essence of the author. And why not, since to author, from the Latin auctor, meaning creator, is a term of animation! The animator would be the author of the author, the auteur of the auteur – not only the master and commander, the ruler/controller, of all within his dominion but its absolute creator, a figure fashioned in the mold of God himself, creator/animator of the universe and all within. In such a divine light, the human animator is envisioned as supreme human being, individual, master, who gives birth to worlds, to universes, made to his measure – Romantic and existential hero, humanist individual, pure origin, pure punctual source, pure unified subject, pure subjectivity, pure intentionality, pure autonomy, par excellence; and what he engenders, what he originates – thanks to frame by frame construction, that modality that animation theorists claim as what uniquely defines animation – is his total, pure creation.10 ‘Against’ this article of faith in and of animation studies, ‘against’ this purist, utopian, idealist, mythicising ontology of the animator as singular master, as auteur, we raise not only the challenges to it of ‘poststructuralist’ and ‘postmodernist’ thought but those akin to such ‘thought’ that go by the name of the great decenterers and decenterings of the human species and/or individual in the history of the world: our list includes Copernicus, Darwin, Marx, Nietzsche, Freud, Einstein, quantum mechanics, quantum cosmology, chaos theory, cybernetics, systems theory, computer codes, molecular biology (the DNA code), robotics, structuralism, semiology, etc. With each of these approaches, the human no longer stands at the centre, sovereign, all-controlling and alone, no longer stands exempt from and master of the object, the world, the universe – the animation universe. In 1917 Freud mobilised three of these great decenterings in his key essay ‘A Difficulty in the Path of Psycho-analysis’, calling them ‘the three blows’ to man’s narcissism, his self-love: Copernicus’ cosmological death blow, death blow to geocentrism; Darwin’s biological death blow, death blow to anthrocentrism; and Freud’s own psychological death blow, death blow to egocentrism, the unconscious as death blow to the self as unified, as full consciousness master of itself, indeed death blow to the omnipotence and omniscience of thought he Freud arguably projected onto primitives. So, as with my proposal of a quantum cosmological Cryptic Complex in ‘The Nutty Universe of Animation, the “Discipline” of All “Disciplines”, And That’s Not All, Folks!’ (Cholodenko, 2006), a cosmological death blow forever denying humans a Theory of Everything, hence mastery of the universe, indeed as in all my work, I privilege an other reading, one in league with these great decenterings, one deconstructing and seducing not only the sovereignty, the mastery, of the human but the human ‘as such’, as well as the individual, identity and self-identity, hence the model of the animator as auteur, the master individual, identity and self-identity, and that does so with (reference to and by mobilizing) the very logics, processes, and operations of animation, of the animatic – of the nutty animatic universe. In the animatic universe, even as animation is prior to and animator of all disciplines, the animatic is prior to and ‘animator’ of all animation, with the most profoundly deconstructive and seductive consequences therefore for not only animation but all disciplines, individually and collectively, indeed for all entities conceived of as entire unto and master of themselves. Another key deconstructive text which we can consider – like Freud’s, ghosting and ghosted by the title of this article – is Roland Barthes’ famous, provocatively titled 1968 essay ‘The Death of the Author’. That essay circumscribes for us the death of the animator as author and author as animator, but with this qualification: for us, Barthes does not simply liquidate the Author to reanimate him as the Reader. Rather, Barthes sets in train the reanimation of both Reader and Author as spectres, spectres ghosting and ghosted by, cryptically incorporated in and cryptically incorporating, the text, the text for Derrida veritably ‘a lodging, the haunt of a host of ghosts’ (Derrida, 1986, xxiii), making both reader and author, like the text ‘itself’, spectral animators animating animatically with their lifedeath, turning spectatorship – of both author and reader – into spectreship. Do we need to say that such an author, reinstated as spectre, is by definition impossible to track down?11 To Descartes’ famous dictum, ‘I think, therefore I am’, Freud responded: ‘The ego is not master in its own house’ (Freud, 1955, 143), the mind. Even as Jacques Lacan will come to say: ‘I is an other’ (‘Je est un autre’) (Lacan, 1991 p.7). As Baudrillard will speak of ‘a sort of invention of the subject by the object’, where ‘the object becomes the horizon of the subject’s disappearance’ (Baudrillard, 2000 pp.76-77). Insofar as psuché spectres psyche as mind, it makes of thoughts ghosts. And insofar as for us Freud’s house of the ego is crypt, haunted house, house of uncanny, spectral, cryptic incorporations, whose paradigmatic model for us is the cinema, is film animation as the animatic, it is not the ego but psuché, the spectre, death as lifedeath, that is ‘master’ in this house. Or, as Renfield says of Dracula, ‘The master comes’, a master who is for us never not returned and returning. Oh, yes, the felicity of Felix. To the perennial question bedevilling animation scholars – who animated, authored, originated Felix? – Pat Sullivan or Otto Messmer? – for us, Felix is the very answer to the question. The felicity of Felix is that, as a figure of metamorphosis, of plasmaticness, as Eisenstein called the ‘essence’ of animation – that formless form that, giving all form, is itself never givable ‘as such’ – as figure therefore of the animatic, he gives the lie to any attempt to fix, arrest, isolate and thereby render inanimate (such a figure of) animation in any particular creator/animator/author of him, in any determinate origin. Felix exemplifies and performs animation, the animatic, in the at once necessity and impossibility of defining, finalising on, resolving, an origin, including of animation. In this sense, plasmaticness, the animatic, would be that nothing that enables and at the same time disenables everything, a nothing that would include not only the human animator’s ‘self-figuration’ (Crafton, 1982 p.11) – Donald Crafton’s term for that distinctive feature of the animated film, the animator’s ‘interjecting’ himself as a kind of self-projection into the film – but, to recast Crafton’s term, the animatic apparatus’ ‘“self”-figuring’(!) in film animation. What lies for us before and beyond that projection, as it lies before and beyond introjection, is cryptic incorporation, the crypt, the haunted house, of cinema, a crypt, a haunted house, turning all into spectres, including ‘itself’. Notes 1 The title of this paper is to be read ‘Death the Animator, the Death of the Animator, or: The Felicity of Felix’. 2 The first part of this paper, subtitled ‘Kingdom of Shadows’, was presented at the Animated Dialogues conference in Melbourne 17-19 June, 2007. 3 For an analysis of a singular precedent for us for such a turn, see Jacques Lacan’s treatment of the anamorphic skull in Hans Holbein’s famous painting The Ambassadors (1533) in his The Four Fundamental Concepts of Psycho-Analysis, and Slavoj Žižek’s treatment of it after Lacan in Looking Awry. 4 Inherited in all ontologies of cinema, most famously André Bazin’s. 5 Indeed, Vernant writes, ‘The psuché is a nothing, an empty thing, an ungraspable evanescence, a shade…’ (1991 p.189) 6 On animation as ‘blind spot’ of cinema and media studies, see my ‘Animation – Film and Media Studies’ “Blind Spot”’, published in the Society for Animation Studies Newsletter, vol. 20, no. 1, Spring 2007. The notion of ‘blind spot’, and of animation as ‘blind spot’, posited here is radically different from what is broached there. In the sense posited here, blind spot is that device that is at once unseen, in fact is never seen, but that allows one to see, is the very condition of possibility of ‘sight’ – the blindness that make sight at once possible and impossible. In such a light, animation becomes the blind spot of the blind spot, the blind spot ‘as such’. No longer something Film Studies, or anything or anybody, for that matter, does not wish to see but rather can not, can never, see, wish to or not. By the by, that blind spot makes seeing oneself seeing oneself – the very premise of self-reflexivity, of auto-reflection – impossible per se. 7 In other words, he saw Death in its penultimate form, as did the soldier who unexpectedly encountered Death in the marketplace before his rendez-vous with Death in Samarkand, a tale related by Baudrillard in his book Seduction. 8 Indeed, for us, Deleuze’s definition in Cinema 1: The Movement-Image, trans. Hugh Tomlinson and Barbara Habberjam (London: The Athlone Press, 1986), p. 5, of how the cartoon film, that is, animation, can be cinema is a definition of how cinema is animation(!) – a definition for us that is remarkably avatar of Norman McLaren’s famous one – even as Deleuze makes the time-image ‘the phantom which has always haunted the cinema…’ (Cinema 2: The Time-Image, trans. Hugh Tomlinson and Robert Galeta (Minneapolis: University of Minnesota Press, 1989), p. 41), haunting, strangely returning to and reanimating his movement-image, which is never not time-image for him. In other words, for Deleuze cinema is never not spectre, never not for us therefore of the order of animation as the animatic. 9 This limitation is typical of Anglo-American Film Studies, too. See my Introduction to THE ILLUSION OF LIFE: Essays on Animation (Sydney: Power Publications in association with the Australian Film Commission, 1991), pp. 14 and 21, and my ‘“OBJECTS IN MIRROR ARE CLOSER THAN THEY APPEAR”: The Virtual Reality of Jurassic Park and Jean Baudrillard’, in Jean Baudrillard, Art and Artefact, ed. Nicholas Zurbrugg (London: Sage Publications, 1997), pp. 82-83, note 19, republished in International Journal of Baudrillard Studies, vol. 2, no. 1, January 2005, on the web. (http://www.ubishops.ca/baudrillardstudies/). 10 For our critique of the ontologising of frame-by-frame construction, see the Introduction to THE ILLUSION OF LIFE, p. 36, note 34, and my ‘Who Framed Roger Rabbit, or The Framing of Animation’ essay in the book, p. 237, note 13. For other responses to that construction, consult the essays in THE ILLUSION OF LIFE 2: More Essays on Animation (Sydney: Power Publications, 2007) by Pauline Moore and Annemarie Jonson. 11 See the Introduction to THE ILLUSION OF LIFE 2, p. 83, note 65, which this last paragraph extends and complicates in terms of Barthes’ article. That note also references several key thinkers in animation studies who promulgate the orthodox notion of the sovereignty and total control of the animation auteur. Alan Cholodenko is former Head of Department and Senior Lecturer in Film and Animation Studies in the Department of Art History and Film Studies at the University of Sydney, where he now holds the title of Honorary Associate. This paper was originally presented at the Society for Animation Studies Conference in Portland, Oregon in July 2007. Bibliography Barthes, R. (1977), ‘The Death of the Author’, Image-Music-Text, Hill & Wang, New York. Baudrillard, J. (2000), The Vital Illusion, Columbia University Press, New York. Baudrillard, J. (2001), Impossible Exchange, Verso, London. Cholodenko, A. (1991), Introduction to A. Cholodenko (ed), THE ILLUSION OF LIFE: Essays on Animation, Power Publications in association with the Australian Film Commission, Sydney. Cholodenko, A. (1991), ‘Who Framed Roger Rabbit, or The Framing of Animation’, in A Cholodenko (ed), THE ILLUSION OF LIFE: Essays on Animation, Power Publications in association with the Australian Film Commission, Sydney. Cholodenko, A. (1997), ‘“OBJECTS IN MIRROR ARE CLOSER THAN THEY APPEAR”: The Virtual Reality of Jurassic Park and Jean Baudrillard’, in N. Zurbrugg (ed), Jean Baudrillard, Art and Artefact, Sage Publications, London, republished 2005 in International Journal of Baudrillard Studies, vol. 2, no. 1, January, Bishops’ University, Canada (http://wwwubishops.ca/baudrillardstudies/). Cholodenko, A. (2004) ‘The Crypt, the Haunted House, of Cinema’, Cultural Studies Review, vol. 10, no. 2, September 2004. Cholodenko, A. (2006), ‘The Nutty Universe of Animation, the “Discipline” of All “Disciplines”, And That’s Not All, Folks!’, International Journal of Baudrillard Studies, vol. 3, no. 1, January, Bishops’ University, Canada (http://wwwubishops.ca/baudrillardstudies/). Cholodenko, A. (2007), (ed) THE ILLUSION OF LIFE 2: More Essays on Animation, Power Publications, Sydney. Cholodenko, A. (2007), ‘Animation – Film and Media Studies’ “Blind Spot”’, Society for Animation Studies Newsletter, vol. 20, no. 1, Spring (http://gertie.animationstudies.org) Crafton, D. (1982), Before Mickey: The Animated Film 1898-1928, The MIT Press, Cambridge, MA. Deleuze, G. (1986), Cinema 1: The Movement-Image, The Athlone Press, London. Deleuze, G. (1989), Cinema 2: The Time-Image, University of Minnesota Press, Minneapolis. Derrida, J. (1986), ‘Fors’, in N Abraham & M Torok, The Wolf Man’s Magic Word: A Cryptonomy, University of Minnesota Press, Minneapolis. Freud, S. (1955), ‘A Difficulty in the Path of Psycho-analysis’, in Freud, S, Standard Edition, vol. 17, The Hogarth Press & The Institute of Psycho-Analysis, London. Gorky, M. (1996), quoted in C Harding & S Popple, In the Kingdom of Shadows, Cygnus Arts, London. Gunning, T. (1989), ‘An Aesthetic of Astonishment: Early Film and the (In)credulous Spectator’, Art and Text 34, Spring 1989, p. 42 Lacan, J. (1979), The Four Fundamental Concepts of Psycho-Analysis, Penguin, Harmondsworth, England. Lacan, J. (1991), The Seminar of Jacques Lacan, Book II: The Ego in Freud’s Theory and in the Technique of Psychoanalysis, 1954-1955, W.W. Norton and Co., London. Vernant, J.-P. (1991), Mortals and Immortals, Princeton University Press, Princeton. Žižek, S. (1991), Looking Awry: An Introduction to Jacques Lacan through Popular Culture, The MIT Press, Cambridge, Massachusetts. © Alan Cholodenko, 2007 Edited by Nichola Dobson
Keywords: death|Felix|theory